2012
DOI: 10.1152/ajprenal.00247.2012
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-dependent and -independent regulation of the epithelial sodium channel (ENaC) in mouse distal nephron

Abstract: Aldosterone is thought to be the main hormone to stimulate the epithelial sodium channel (ENaC) in the aldosterone-sensitive distal nephron (ASDN) comprising the late distal convoluted tubule (DCT2), the connecting tubule (CNT) and the entire collecting duct (CD). There is immunohistochemical evidence for an axial gradient of ENaC expression along the ASDN with highest expression in the DCT2 and CNT. However, most of our knowledge about renal ENaC function stems from studies in the cortical collecting duct (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 49 publications
9
102
0
Order By: Relevance
“…29,42,43 Our immunofluorescence and functional data are also in good agreement with patch-clamp studies on isolated early and late ASDN segments from AS +/+ and AS 2/2 mice that indicated that ENaC regulation in the early ASDN is largely aldosterone independent. 44 Here, we provide a possible explanation for the aldosterone-independent activity of ENaC in the early ASDN of AS 2/2 mice. AS 2/2 mice have very high 26 This probably does not directly contribute to the regulation of K + homeostasis, but may compensate for the loss of aldosterone at least in part by ensuring a residual ENaC activity in the kidney of AS 2/2 mice.…”
Section: Discussionmentioning
confidence: 70%
“…29,42,43 Our immunofluorescence and functional data are also in good agreement with patch-clamp studies on isolated early and late ASDN segments from AS +/+ and AS 2/2 mice that indicated that ENaC regulation in the early ASDN is largely aldosterone independent. 44 Here, we provide a possible explanation for the aldosterone-independent activity of ENaC in the early ASDN of AS 2/2 mice. AS 2/2 mice have very high 26 This probably does not directly contribute to the regulation of K + homeostasis, but may compensate for the loss of aldosterone at least in part by ensuring a residual ENaC activity in the kidney of AS 2/2 mice.…”
Section: Discussionmentioning
confidence: 70%
“…We speculate that the higher baseline potential difference and hence, equivalent current, and the insensitivity to aldosterone observed with primary cells in mpkCCD c14 media may have favored a DCT2/CNT phenotype. In contrast, cells incubated with REBM, which exhibited a lower baseline but higher aldosterone-stimulated sodium current, resembled a CCD phenotype (43). REBM has three known differences from mpkCCD c14 media: 1) a lack of supplemental selenium; 2) substitution of dexamethasone with hydrocortisone; and 3) the presence of epinephrine.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, expression of markers for the proximal tubule, including SGLT2 and GLUT2 (65), was significantly enriched in unbound preparations. Surprisingly, expression of markers for the distal cortical tubule, including NCC (DCT1 and DCT2), TRPM6 (DCT1 Ͼ DCT2) (72), ENaC (DCT2 to principal cells of the CNT and CCD) (43), and pendrin (intercalated cells from CCD) (25,40), were enriched in DBA-bound preparations. This was unexpected because DBA staining by immunofluorescence microscopy was much stronger in only CNT and CCD (Fig.…”
Section: Dba-linked Biotin Selectively Binds the Connecting Tubulementioning
confidence: 97%
“…However, we do not exclude that the CD may still play an important role under challenging conditions, even if ENaC deletion per se in this segment does not seem to be a prerequisite for sodium and potassium balance. 7 Indeed, two recent studies unveil an ENaC regulation largely independent from aldosterone 17 and likely dependent on vasopressin, 31 suggesting that sodium but also, potassium handling might be regulated in a cell type-and nephron segment-specific manner. In conclusion, Scnn1a…”
Section: Aldosterone-independent Regulation Of Ncc In Scnn1amentioning
confidence: 99%